Calorie- and protein-deficient diets despite adequate dietary diversity among pregnant women in a low-income urban area in Delhi, India - Saurav Basu; Anjali Rajeev; Aanchal Anand; Samar Hossain; Mongjam M Singh (Wolters Kluwer Medknow Publications, 2022)
We interviewed 221 antenatal women in the second or third trimester of pregnancy attending a primary care antenatal clinic at a low-income area in Delhi, India, during 2019-20. The Minimum Dietary Diversity-Women (MDD-W) score for 10 food groups was calculated using the open recall method during a 24-h recall period. The median MDD-W score was 6 (IQR 4-7). Low dietary diversity (MDD-W <5) was observed in 65 (29.4%) participants. Low SES and higher age (≥25 years) were statistically significant predictors of lower dietary diversity, but it was unrelated to parity. Furthermore, protein deficit was observed in 185 (83.7%) and calorie deficit in 210 (95%) participants.